Overall Satisfaction among the Managers of PADBs Regarding the Working of Punjab Co-operative Agricultural and Rural Development Bank - Rajni (Gyan Management Journal, 2015)
The Punjab State Co-operative agricultural and rural development bank is playing an important role in meeting credit requirement of rural population in the state. Present study make an attempt to know the overall satisfaction of managers of PADBs regarding working of State Cooperative Agricultural Development Bank by using statistical tools like, mean, standard deviation, Chi-square, AN OVA, F-ratio, t- value and multiple regression for which primary data has been collected through pre-designed questionnaire. Overall level of satisfaction among managers is not affected by division, age and qualification but it is significantly influenced by the job experience. The combined effect of demographic variables on overall level of satisfaction has been analysed by using multivariate analysis and found age and job experience are significantly positive contributors of overall level of satisfaction among managers in PADBs in Punjab.